Relasi Persahabatan dalam Kajian Komunikasi Antar Budaya - Sudarmika, Dina (Oratio Directa (Prodi Ilmu Komunikasi), 2024)
Abstract Friendship is one of the most valuable relationships for humans. Friendship in the study of intercultural communication can be interpreted as the relationship that exists between people who have different cultural backgrounds. Intercultural friendship can result in positive attitude changes, such as increased cultural understanding, acceptance, and self-reflection. For this reason, this study aims to describe and explain how the relationship of friendship in environmental lecturers at Karno University from the perspective of similarity attraction theory. The research technique used is qualitative descriptive. Data was collected through two instruments, there are: participatory observation and documentation of six participants. This study concludes that friendship relationships from the perspective of similarity attraction theory which explains that friendship relationships built by members of the lecturer friendship group at Karno University are based on values and beliefs, attitudes, cultural backgrounds, and interests, so that they complement each other despite differences in cultural backgrounds.Keywords: Friendship Relations, Intercultural Communication, Similarity Attraction.